DEVELOPMENT OF OXYGEN CONSUMPTION PREDICTION MODEL AND PHYSICAL WORKLOAD EVALUATION OF INDONESIAN BUILDING CONSTRUCTION WORKERS - KEVIN TOPAYUNG, PRIATNO
Construction workers perform physically demanding work and require a large amount of energy metabolism. Such work causes negative impacts such as chronic fatigue, decreased cardiovascular function and productivity. Evaluation of physical workload is necessary to prevent these negative impacts. The purpose of this study was to develop a prediction model of occupational oxygen consumption (VO2) and evaluate the physical workload of Indonesian building construction workers. The prediction model consisted of one predictor, percentage heart rate (%HRR). The study participants were 26 people with ages ranging from 19 to 61 years. The study measured oxygen consumption (VO2) and heart rate (HR) in the laboratory using the maximal method. The protocol used was the Bruce protocol. Participants walked to run on a treadmill to the maximum limit. The highest oxygen consumption value of treadmill testing is VO2max . Seven treadmill workload intensities (%HRR) (25%, 35%, 45%, 55%, 65%, 75%, and 85%) were used as predictors in the oxygen consumption (VO2) prediction model. Physical workload measurements used percentage heart rate (%HRR) and Borg's rating of perceived exertion scale (RPE). Work VO2 was obtained by inputting %HRR into the prediction model. Evaluation of physical workload using %VO2max and %HRR. The results showed that the average VO2max of workers was 3.25 ± 0.78 l/min or 57.49 ± 11.65 ml/min/kg. The work VO2 prediction model was - 0.024+(0.032 x %HRR) with R2 0.993. Average physical workload was 18.81% of %VO2max and 31.86% of %HRR. VO2max had a negative effect on physical workload, indicating that the greater the aerobic capacity, the lower the workload experienced by workers. Age and RPE had no significant effect on physical workload. Heart rate (HR) had a very high correlation with VO2 during laboratory testing. Some interventions that can be provided are Management encourages workers to do more strenuous work in the morning rather than during the day. Management distributes tasks to workers who have the appropriate aerobic capacity. Despite its limitations, this study succeeded in formulating a physical workload prediction model for construction workers that is useful for evaluating workload as a basis for improving working conditions.